Trypanosoma cruzi extracellular amastigotes and host cell signaling: more pieces to the puzzle - Ferreira, Éden R.; Bonfim-Melo, Alexis; Mortara, Renato A.; Bahia, Diana (Frontiers in Immunology, 2012)
Among the different infective stages that Trypanosoma cruzi employs to invade cells, extracellular amastigotes have recently gained attention by our group. This is true primarily because these amastigotes are able to infect cultured cells and animals, establishing a sustainable infective cycle. Extracellular amastigotes are thus an excellent means of adaptation and survival for T. cruzi, whose different infective stages each utilize unique mechanisms for attachment and penetration. Here we discuss some features of host cell invasion by extracellular amastigotes and the associated host cell signaling events that occur as part of the process.